Ausência de associação entre os polimorfismos do gene interleucina-18 e artrite reumatoide - Farias, Ticiana Della Justina; Do Cantoa, Luisa Matos; Medeiros, Mayara Delagnelo; Sereia, Aline Fernanda Rodrigues; Back, Lia Kubelka Fernandes de Carlos; De Mello, Filipe Martins; Zimmermann, Adriana Fontes; Pereira, Ivânio Alves; Muniz, Yara Costa Netto; Marrero, Andrea Rita; De Souza, Ilíada Rainha (Springer Nature, 2013)
Objective: To assess the association of the polymorphisms of the interleukin-18 (IL-18) gene with rheumatoid arthritis (RA) and with risk factors for cardiovascular diseases (CVD). Methods: This sample comprised 97 patients with RA and 151 healthy controls. In the patients, risk factors for CVD were analyzed, such as cholesterol levels, arterial hypertension, smoking habit, C-reactive protein (CRP) level, and rheumatoid factor. DNA was extracted and the single nucleotide polymorphisms (SNP) at the -607C/A and -137G/C positions of the IL-18 gene were assessed in both groups. The Hardy-Weinberg equilibrium (HWE) was calculated and the odds ratio (OR) test performed, considering a 95% CI and P < 0.05. Results: The frequencies of the -607A allele in patients with RA and in controls were 0,443 and 0.424, respectively, and of the -137C allele, 0.304 and 0.291, respectively. The genotype frequencies were in HWE, except for controls in the -137 locus (P = 0.006). Association of the polymorphisms of the IL-18 gene was found with neither RA nor risk factors for CVD, including cholesterol level and CRP (P > 0.05). In addition, more smokers were found among patients with RA as compared with controls (OR = 1.691; P = 0.088), and the CRP levels were slightly higher in patients who smoked than in patients who did not (OR = 2.673; P = 0.061). Conclusions: In this sample of patients with RA in the South of Brazil, association of the polymorphisms of the IL-18 gene was observed with neither RA nor risk factors for CVD. ©2013 Elsevier Editora Ltda.
Lack of association between interleukin-18 polymorphisms and rheumatoid arthritis
Keywords: Brazil; Cardiovascular diseases; Gene polymorphism; Interleukin-18; Rheumatoid arthritis